KONFLIK PADA ACARA ORGEN TUNGGAL DI NAGARI ABAI SIAT KECAMATAN KOTO BESAR KABUPATEN DHARMASRAYA - Hasanah, Nora Uswatun (Pendidikan Sosiologi, 2014)
Thesis Programs Study Sociology at STKIP PGRI West Sumatra 2014. This research intent to describe about Conflict On Keyboard Sound At the Nagari Abai Siat, Subdistrict Koto Besar, Kabupaten Dharmasraya. Theory that used in research is by use of conflict theory that interposed by Lewis Coser. This research constitute qualitative research by using descriptive analisis. the Result of the observation show that: (1 ) happening conflicting form on Keyboard Sound at Nagari Abai Siat constitutes in violence form as mutually hits, (2 ) conflict factors which is liquor, so long dislike, and snatches rise onto stage, (3) conflict were started at 00:00 WIB (4 ) conflicting Impacts which is society are not comfortble, people do conflict party painfulness, and family that arranges to hand down Keyboard Sound perceives not comfortble. (5) conflicting resolution to be done by mark sense conflicting rev mechanisms by niniak mamak , Wali Nagari Abai Siat by gives severally sanction and police force party go along in give safety and instruction.